Memahami Bidang Garapan Personalia Pendidikan dalam Administrasi Pendidikan - Humairoh Sakinah Zainuri; Khoiriah Marta Parapat; Nadia Safitri (Universitas 45 Surabaya, 2024)
In order to achieve educational goals optimally, effectively and efficiently, the educational process cannot be separated from education management. Education management is divided into several fields, one of which is the field of educational personnel. Personnel are all members of the organization who work for the benefit of the organization, namely to achieve the goals that have been determined. The field of personnel development is also called the entire structuring process that is related to the problem of obtaining and using labor to achieve the goals of the school that have been predetermined. The purpose of the field of educational personnel is to utilize labor effectively and efficiently to achieve maximum results, which is in the form of a result, product or production. Personnel administration consists of two types, namely educational personnel and non-educational personnel. The importance of personnel management in improving the quality of education is the main key to the success of achieving educational goals. Personnel are required to know the potential that exists around them and utilize them effectively and efficiently to improve the quality of education in schools.